Conventional endovascular treatment and flow diverter for unruptured small- and medium-sized paraophthalmic segment aneurysms - Liu, Kefeng; Sun, Yong; Liu, Fang; Zhang, Xin; Li, Aimin (Frontiers in Neurology, 2025)
ObjectiveThe efficacy and safety of flow diverters (FD) compared to conventional endovascular treatment (CET) for treating small- and medium-sized intracranial aneurysms remain unclear. This study aimed to compare the efficacy and safety of FD and CET in common small- and medium-sized paraophthalmic segment aneurysms (PSAs) in clinical practice, with the expectation of providing a basis for clinical treatment decisions for such aneurysms.MethodsThis multicenter, retrospective cohort study included consecutive patients with unruptured small- and medium-sized (≤10 mm) PSAs treated at three neurosurgical centers between January 2018 and December 2023. Patients were assigned to the CET or FD group. The primary efficacy endpoint was the rate of complete aneurysm occlusion. The safety endpoints included perioperative and postoperative complications. Propensity score matching (PSM) was used to verify the stability of the results. Subgroup analyses were conducted to identify the factors influencing clinical outcomes.ResultsA total of 688 PSAs in 601 patients were analyzed, with 595 cases treated with CET and 93 cases treated with FD. The mean follow-up duration for all cases was 12.6 ± 12.9 months. The complete occlusion rate was significantly higher in the CET group than in the FD group (98.2% versus 66.7%, p < 0.001) at the last follow-up. However, the cumulative incidence of aneurysm occlusion increased over time in both groups, with no significant difference between the groups (log-rank test, p = 0.261). Compared with the CET group, the adjusted hazard ratio (HR) for complete occlusion in the FD group was 0.632 (95% confidence interval [CI]: 0.307–1.299; p = 0.212). The FD group had a higher overall complication rate (12.0% versus 1.1%; p = 0.007); nevertheless, these complications did not significantly affect long-term functional outcomes. The findings remained robust after PSM. Subgroup analysis revealed that the efficacy advantage of CET was more prominent in older patients (≥ 65 years).ConclusionThe rates of complete occlusion for small- and medium-sized PSAs were not significantly different between CET and FD therapy. However, the procedural safety profile of FD requires careful consideration. CET demonstrated a more pronounced therapeutic benefit in elderly patients than in younger patients.